Effect of treatment with Lactococcus lactis NZ9000 on intestinal microbiota and mucosal immune responses against Clostridium perfringens in broiler chickens - Boodhoo, Nitish; Shojadoost, Bahram; Alizadeh, Mohammadali; Astill, Jake; Behboudi, Shahriar; Sharif, Shayan (Frontiers in Microbiology, 2023)
Alterations in intestinal microbiota can modulate the developing avian intestinal immune system and, subsequently, may impact on resistance to enteric pathogens. The aim was to demonstrate that early life exposure to Lactococcus lactis, could affect either susceptibility or resistance of broilers to necrotic enteritis (NE). L. lactis NZ9000 (rL. lactis) pre-treatment at 1, 7, 14 and 21 days of age (DOA) led to a significant decrease in NE lesion scores in Clostridium perfringens infected chickens. C. perfringens Infection was associated with spatial and temporal decreases in mononuclear phagocytes and CD4+ αβ T cells. However, rL. Lactis pre-treatment and subsequent C. perfringens infection led to a significant increase in mononuclear phagocytes, CD8α+ γδ T, αβ T cells (CD4+ and CD8α+) and B cells (IgM+, IgA+ and IgY+), as well as IL-12p40, IFN-γ and CD40. Differential expression of interleukin (IL)-6, IL-8, IL-10, IL-13, IL-18, IL-22, and transforming growth factor (TGF)-β were observed in L. lactis treated chickens when compared to C. perfringens infected chickens. Microbiota analysis in C. perfringens infected chickens demonstrated an increase in abundance of Bacillota, Bacteroidota, Pseudomonadota and Actinomycetota. These findings suggests that modulation of the chicken intestinal immune system by L. lactis confers partial protection 30 against NE 1